MILITARY LEADERSHIP DEVELOPMENT IN THE DIGITAL ERA - Dudung Abdurachman (SEAN Institute, 2022)
Military leadership has a crucial role in ensuring the effectiveness and adaptability of military organizations in facing changing times, including changes caused by the digital era. This research aims to examine the concept of military leadership and aspects of military leadership development in the digital era at the level of the concepts of loyalty and conflict of interest which are the main elements in military leadership. This research methodology involves in-depth literature analysis, using a qualitative descriptive approach. The results of this research highlight the key role of military leadership in facing a digital era full of challenges. In particular, military leaders need to ensure a strong understanding of the nation's values and philosophy among their ranks, by leveraging online education and training as well as digital platforms to maintain and strengthen loyalty. Additionally, conflict of interest monitoring and effective online reporting systems are an important part of maintaining integrity in an increasingly connected military environment. The use of technology also plays a role in increasing understanding of values through digital education and training as well as virtual military simulations. Additionally, the importance of cybersecurity as a top priority should not be overlooked, with cybersecurity training and implementation of strict security policies being key in maintaining the integrity of military operations.